Le mutilazioni genitali femminili tra misure di prevenzione e di contrasto: prospettive per l’eradicazione del fenomeno in Italia (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Brevi considerazioni introduttive - 2. Mutilazioni genitali femminili: una questione anche italiana - 3. Profili risarcitori e misure repressive: il quadro normativo italiano - 4. Art. 583 bis c.p.: riflessioni sulla formulazione della norma - 5. Strategie integrate, approccio globale e multisettoriale nella lotta al fenomeno - 6. Inclusione sociale, sensibilizzazione delle coscienze e metamorfosi delle condotte nella strada maestra della prevenzione - 7. Politiche assistenziali e misure di protezione delle donne a rischio e delle vittime nelle strategie di prevenzione.FGM between prevention and contrast measures: eradication perspectives of the phenomenon in Italy.ABSTRACT: FGM includes practices of total or partial cutting or external genital lesions of women for no therapeutic reason. They are carried aut for socio-cultural or hygienic-prophylactic causes. Moreover, these rituals are also practiced by some religious communities despite the lack of impositive precepts in sacred texts. FGM is also widespread in Italy and it is constitute a violation of women’s human rights and child abuse. The Italian State fights the phenomenon with external and internal actions, through strategic measures of prevention, protection and assistance for victims. FGM does not exclude compensation for damage to the health of the women involved. In Italy, a new type of crime has been introduced with the art. 583 bis c.p. However, the rule has not been widely applied. This issue needs to faced up on a global level. Above all, it is necessary to persuade those who follow the practice to be the main actors of their own change.
Keywords: Tutela penale e fattore religioso